2005
DOI: 10.1089/ten.2005.11.415
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Effects on Rat Hepatocyte Spheroid Formation and Function

Abstract: Hepatocytes cultured on moderately adhesive surfaces or in spinner flasks spontaneously self-assemble into spherical tissue-like aggregates (spheroids). These spheroids have smooth surfaces and tissue-like polarized cell morphology, including bile canalicular-like channels, and maintain high viability and liver-specific functions for extended culture periods. Dexamethasone (DEX), a synthetic glucocorticoid, is known to elicit various responses in gene expression, and is often added to hepatocyte culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
1
11
2
1
Order By: Relevance
“…Although the underlying mechanism is unclear, this result is consistent with one report using suspension cultures in spinner flasks. 25 This prior publication also reported a higher albumin secretion rate with Dex, which agrees with our data showing that albumin production was increased in the presence of Dex for all culture configurations. The albumin gene promoter region is known to have a glucocorticoid response element, which may mediate this observed increase.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Although the underlying mechanism is unclear, this result is consistent with one report using suspension cultures in spinner flasks. 25 This prior publication also reported a higher albumin secretion rate with Dex, which agrees with our data showing that albumin production was increased in the presence of Dex for all culture configurations. The albumin gene promoter region is known to have a glucocorticoid response element, which may mediate this observed increase.…”
supporting
confidence: 92%
“…26 Another possible explanation may be due to the antiinflammatory properties of Dex, which may reverse albumin suppression induced by a proinflammatory or acute phase response triggered by the isolation procedure. 27 On the contrary, we did not observe more urea production in the presence of Dex, unlike what was reported by Abu-Absi et al 25 Interestingly, Dex had no effect on the CYP450 activity in PuraMatrix cultures, but inhibited the recovery of CYP450 function beyond day 4 in the two culture configurations using type I collagen. Clearly, the effects of Dex on hepatic functions in hepatocyte in vitro culture remain to be elucidated; however, we propose that including 0.1 mM Dex in the hepatocyte culture medium for the first 3 to 4 days after seeding is an efficient way to control the size of the spheroids on PuraMatrix and help cells recover from isolation injury.…”
contrasting
confidence: 78%
“…On the basis of our results, we hypothesized that the endocrine control exerted by GCs on YAP might have an impact in sustaining the self-renewal potential of breast CSCs35. To assess whether the GR–YAP axis plays a causal role in defining CSC traits, we tested the effect of BM on the self-renewal potential of mammary epithelial cells from a panel of different basal breast cancer cell lines by testing their capacity to form and propagate mammospheres in vitro 363738.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte spheroids ranging from 50 to 100 μm were formed between 2 and 3 days in the conventional method. 18, 20 In the present study, hepatocyte spheroids in the nanosphere method formed between 24 and 36 h. The higher cell viability in the nanosphere‐added cultures may be due to the increased speed at which the spheroids formed and the higher efficiency of hepatocyte spheroid formation, since single hepatocytes in suspension die rapidly 18, 24. Our previous studies have demonstrated that the formation of cell spheroids using nanospheres enhanced the rate of cell aggregation, subsequent growth of the aggregated cells, and the production of a recombinant protein more than the cell spheroid formations without nanospheres 22–24.…”
Section: Discussionmentioning
confidence: 99%